Digital Technologies and Information Systems in Social Innovation Ecosystems - Albuquerque, Beatriz Ventorini Lins de; Siqueira, Sean Wolfgand Matsui (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: The Global Digital Compact, signed in 2024, emphasizes cross-sector collaboration and recognizes science, technology, and innovation as pillars for accelerating the achievement of the Sustainable Development Goals (SDGs). Problem: Despite the growing recognition of digital technologies and information systems (IS) in advancing the SDGs, there is limited understanding of how these technologies are effectively employed in social innovation ecosystems (SIEs). This gap may hinder the articulation and sharing of innovation capabilities. Solution: This study aims to map how digital technologies and IS are employed in SIEs and their alignment with the eight priority technologies outlined by the United Nations (UN). IS Theories: Grounded in Dynamic Capabilities Theory and Social Innovation Ecosystems. Method: A systematic mapping study with an exploratory approach, following the SEGRESS framework. A total of 28 primary studies were analyzed from 176 selected across five digital libraries (Scopus, ScienceDirect, Compendex, SciELO, and SBC OpenLib), using qualitative data analysis. Summary of Results: The study identified 38 technologies used in SIEs, covering 13 different types of SIEs. However, only five of the eight priority technology categories defined by the UN were represented. Additionally, the findings suggest that all three dimensions of dynamic capabilities remain underdeveloped within the identified SIEs. Contributions and Impact in the IS Field: This study contributes to GranDSI Br 2016–2026, particularly in Methodologies and Technologies for Citizen Participation. It frames SIEs as key actors in addressing complex social challenges and provides a comprehensive overview of digital technology adoption, highlighting challenges and opportunities for strengthening technological capabilities to accelerate progress toward the SDGs across the dimensions of technology, organizations, and people.